THE CONCEPTS OF HAPPINESS, VIRTUE, AND HONESTY IN LINGUISTICS AND THEIR EXPRESSION IN ENGLISH AND UZBEKISTAN - Mahmudova Dilnoza (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article is devoted to the concepts of Happiness, Virtue, and Honesty in linguistics and their expression in English and Uzbek.  Also, this article reveals the similarities and differences of the concept of "Honesty" in English and Uzbek linguistic culture.  The main and important features of the lexeme of honesty should be called the universal nature of the lexeme of honesty, which puts morality above the interests of a narrow group, ideological or practical thoughts, corporatism, reflecting the objective content of norms.